Implementation of Risk Management in Micro and Small Enterprises: Case Study at Kota Ternate - Zain, Zandy Pratama; Situru, Agatha Christy; Rusandry; Maulana, Syahrial (MANDAR: Management Development and Applied Research Journal, 2025)
Ternate city as a trading hub in North Maluku, holds great potential as well as its own challenges for MSMEs. This study aims to determine how MSME business actors in Ternate City review risks, implement risk management strategies, and maintain their businesses amidst current market competition. This research uses a qualitative method with data collection techniques through interviews. Based on the results of interviews with each MSME business actor, they face various risks, one of which is unsold or easily damaged products, which can be a significant obstacle if not managed properly. In addition, in facing competition, promoting through social media is an effective step. Products in high demand can boost revenue, but careful attention must be paid to inventory management and quality. A good promotional strategy can attract market attention. The implication of this study shows that MSME business actors are said to be successful if they have the ability to manage risks and take advantage of market opportunities, not only in terms of product quality